Predicting Early Disease Recurrence of Pancreatic Cancer following Surgery: Determining the Role of NUDT15 as a Prognostic Biomarker - Daniel Llwyd Hughes; Frances Willenbrock; Zahir Soonawalla; Somnath Mukherjee; Eric O’Neill (Current Oncology, 2022)
Surgical resection remains the only curative treatment strategy for Pancreatic Ductal Adenocarcinoma (PDAC). A proportion of patients succumb to early disease recurrence post-operatively despite receiving adjuvant chemotherapy. The ability to identify these high-risk individuals at their initial diagnosis, prior to surgery, could potentially alter their treatment algorithm. This unique patient cohort may benefit from neo-adjuvant chemotherapy, even in the context of resectable disease, as this may secure systemic control over their disease burden. It may also improve patient selection for surgery. Using the Cancer Genome Atlas dataset, we first confirmed the poor overall survival associated with early disease recurrence (p < 0.0001). The transcriptomic profiles of these tumours were analysed, and we identified key aberrant signalling pathways involved in early disease relapse; downregulation across several immune signalling pathways was noted. Differentially expressed genes that could serve as biomarkers were identified (BPI, C6orf58, CD177, MCM7 and NUDT15). Receiver operating characteristic curves were constructed in order to identify biomarkers with a high diagnostic ability to identify patients who developed early disease recurrence. NUDT15 expression had the highest discriminatory capability as a biomarker (AUC 80.8%). Its expression was confirmed and validated in an independent cohort of patients with resected PDAC (n = 13). Patients who developed an early recurrence had a statistically higher tumour expression of NUDT15 when compared to patients who did not recur early (p < 0.01). Our results suggest that NUDT15 can be used as a prognostic biomarker that can stratify patients according to their risk of developing early disease recurrence.